2010
DOI: 10.1007/978-3-642-14589-6_45
|View full text |Cite
|
Sign up to set email alerts
|

Providing Scalable Data Services in Ubiquitous Networks

Abstract: Abstract. Topology is a fundamental part of a network that governs connectivity between nodes, the amount of data flow and the efficiency of data flow between nodes. In traditional networks, due to physical limitations, topology remains static for the course of the network operation. Ubiquitous data networks (UDNs), alternatively, are more adaptive and can be configured for changes in their topology. This flexibility in controlling their topology makes them very appealing and an attractive medium for supportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…A systematic and generic approach to the design and operation of networked systems has gained attention in recent publications [1][2][3][4][5][6], following important results in the analysis of networks [7][8]. In some of our recent publications, it has been shown that efficiency and robustness are important considerations in the design of networks, leading to different optimal topologies [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic and generic approach to the design and operation of networked systems has gained attention in recent publications [1][2][3][4][5][6], following important results in the analysis of networks [7][8]. In some of our recent publications, it has been shown that efficiency and robustness are important considerations in the design of networks, leading to different optimal topologies [9][10].…”
Section: Introductionmentioning
confidence: 99%